2001
DOI: 10.1007/bf02287463
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban differences in service use for memory-related problems in older adults

Abstract: The reduced availability of providers and travel difficulties in rural areas may thwart older rural adults from getting the care they need for memory-related problems. The purpose of this study was to determine whether rural-urban differences exist in the probability of any service use of primary care physicians and mental health specialists in a full sample of older adults and in a subset of impaired respondents. In the full sample, rural respondents were 0.66 times as likely (p = .06) to have used primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Although further research is needed to identify causal factors, certainly this finding reflects the fact that public mental health services are mandated by the state, thereby increasing physical access to mental health care in rural localities. The relatively high rate of utilization among rural consumers observed in this study is consistent with a recent study by Chumbler, Cody, Booth & Beck (2001) which found rural elders to be as likely as their urban counterparts to seek mental health services for memory-related problems.…”
Section: Discussionsupporting
confidence: 93%
“…Although further research is needed to identify causal factors, certainly this finding reflects the fact that public mental health services are mandated by the state, thereby increasing physical access to mental health care in rural localities. The relatively high rate of utilization among rural consumers observed in this study is consistent with a recent study by Chumbler, Cody, Booth & Beck (2001) which found rural elders to be as likely as their urban counterparts to seek mental health services for memory-related problems.…”
Section: Discussionsupporting
confidence: 93%
“…In their study of mental healthcare use by 120 older adults (defined as age 55+), Phillips and Murrell (1994) found treatment use to be associated with poorer psychological well-being, more physical health problems, higher levels of unpleasant stressful events, and perceived lack of social support. Furthermore, there is evidence that the current cohort of older rural residents may be as likely as their urban counterparts to receive mental health services when such services are available and accessible (Chumbler, Cody, Booth, & Beck, 2001; Karlin & Norris, 2006).…”
mentioning
confidence: 99%